SPEECH RATE OF OLDER PEOPLE - Teixeira, Erica Gonçalves; Celeste, Letícia Correa; Teixeira, Henrique Gonçalves; Reis, César (Cadernos do IL, 2011)
This research consists primarily of the attempt to better understand the phenomena related to the temporal organization in oral reading of adults and older people in Brazilian Portuguese. In order to do so, readings were collected from one of the excerpts of the corpus EUROM1 for Brazilian Portuguese, with 20 female informants. For the analysis of temporal organization, we studied the following parameters: elocution and articulation time, number of pauses and their time, number of syllables, elocution and articulation rates. We were able to note that there is a statistically significant difference between the two groups observed for all the analyzed parameters (except the one with number of syllables). Therefore, we conclude that the temporal organization is an important aspect of prosody, which may give relevant information in a comparative study.